Kualitas Bangunan, Fasilitas, dan Lokasi Perumahan sebagai Faktor Penentu Tingkat Kepuasan Penghuni - Armanto, Rully; Rasyid, Abdullah; Gunarto, Muji (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
This study aims to explore the role of building quality, facilities, and housing location in determining the level of occupant satisfaction. Using quantitative methods with SEM-Smart PLS analysis techniques, this study analyzes primary and secondary data collected from residents of several housing complexes. The analysis results indicate that housing location significantly affects occupant satisfaction, while building quality and facilities do not show a statistically significant effect. These findings underline the importance of selecting a strategic location in housing development to improve occupant satisfaction. This study suggests that developers pay more attention to the location aspect in housing planning and development to achieve optimal levels of occupant satisfaction. Thus, the results of this study can be a reference for stakeholders in developing policies and strategies to improve housing quality